PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN SEKTOR FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Kholidah SM, Nur Diana; Imama, Lely Shofa (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2024)
The purpose of this research is to examine and analyze the influence of company size, liquidity and sales growth on profitability in pharmaceutical sector companies listed on the Indonesia Stock Exchange. The approach used in this research is quantitative, using secondary data in the form of financial reports. This research is a population study taken from the financial reports of 10 pharmaceutical sector companies for the 2018-2021 period. Data analysis used descriptive analysis, classical assumption test, multiple linear regression, t test, f test and coefficient of determination using the SPSS version 24 program. Research results This shows that company size, liquidity and sales growth simultaneously have a significant effect on profitability. Partially, company size has a significant negative effect on profitability, liquidity has a significant positive effect on profitability, then sales growth has a significant positive effect on profitability in pharmaceutical sector companies listed on the Indonesia Stock Exchange.Keywords: Company Size; Liquidity; Sales Growth; Profitability